A Matter of Balance: A French Perspective on Limited Strikes. Issue 2 (2020) - Jeangène Vilmer, Jean-Baptiste
Abstract: What are the philosophical arguments justifying limited strikes? This essay, as part of the roundtable "The Ethics of Limited Strikes, " adopts a French perspective both because France is, along with the United States and the United Kingdom, one of the states that launched such limited strikes in recent years, and because it developed a limited warfare ethos. There is something specific about such an ethos that makes it particularly receptive to the jus ad vim framework and, therefore, to the issue of limited strikes. This essay also builds on the case of the use (or threat) of limited force in Syria as a response to the country's use of chemical weapons between 2013 and 2018. Presented as a way to "punish" the Syrian regime as much as to "deter" it from using chemical weapons again, these limited strikes are a good illustration of the traditional retributive/preventive dichotomy of penal philosophy. I argue that the moral justification of those strikes should be guided by a consequentialist ethic, preventive rather than retributive. From a consequentialist perspective, limited strikes are justified when they "work"—that is, when they have a deterrent/compellent effect. For that to happen, they need to be credible and imply the potential of an escalation; the challenge being to keep the escalation under control. Carrying the risk of inefficacy at one end of the spectrum and of escalation at the other, limited strikes are indeed a matter of balance.